A selective effect of parietal damage on letter identification in mixed case words. - Braet, W; Humphreys, G (2007)
We investigated the reading of cAsE mIxInG and contrast reduction on word reading in patients with unilateral parietal lesions and attentional deficits. We show that, compared with control participants, the patients produce selective increases in lateralised errors when reading mixed case relative to same case words. However, there were not reliable increases in lateralised errors when words were degraded by low contrast. The patients also showed some increases in contralesional errors at a task aimed at feature processing in words (a gap detection task), but these effects were not increased for mixed case stimuli and errors were reduced relative to the word reading task. The results are consistent with mixed case words stressing attention-demanding letter identification, drawing-out an impairment in the patients in attending to contralesional stimuli. On the other hand, effects of contrast reduction are accommodated without necessarily recruiting attentional processes mediated by the posterior parietal lobe.